2016
DOI: 10.1186/s40665-016-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Microrefuges and the occurrence of thermal specialists: implications for wildlife persistence amidst changing temperatures

Abstract: Background: Contemporary climate change is affecting nearly all biomes, causing shifts in animal distributions, phenology, and persistence. Favorable microclimates may buffer organisms against rapid changes in climate, thereby allowing time for populations to adapt. The degree to which microclimates facilitate the local persistence of climate-sensitive species, however, is largely an open question. We addressed the importance of microrefuges in mammalian thermal specialists, using the American pika (Ochotona p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 78 publications
3
34
0
Order By: Relevance
“…Even after accounting for within‐site variation and variation in habitat conditions, the occupied sites and sites in preferentially used substrates (i.e., pahoehoe and talus; Rodhouse et al., ; Jeffress et al., ; Rodhouse & Hovland, ) exhibited considerably more thermal buffering. These results add to the growing evidence (Hall et al., ; Henry et al., ; Millar & Westfall, ; Millar et al., , ; Rodhouse et al., ; Varner & Dearing, ; Wilkening et al., ) that thermally stable subsurface microrefuges decoupled from regional climates are the mechanism by which American pikas persist in otherwise inhospitable conditions along the range periphery. Our study advances this line of inquiry beyond previous studies that have shown that subsurface microclimates are decoupled from aboveground climates (Hall et al., ; Henry et al., ; Millar et al., , ; Shi et al., ; Varner & Dearing, ) and dispersal habitats (Millar et al., ) by demonstrating important differences in microclimates among used and unused sites and substrate types.…”
Section: Discussionsupporting
confidence: 76%
“…Even after accounting for within‐site variation and variation in habitat conditions, the occupied sites and sites in preferentially used substrates (i.e., pahoehoe and talus; Rodhouse et al., ; Jeffress et al., ; Rodhouse & Hovland, ) exhibited considerably more thermal buffering. These results add to the growing evidence (Hall et al., ; Henry et al., ; Millar & Westfall, ; Millar et al., , ; Rodhouse et al., ; Varner & Dearing, ; Wilkening et al., ) that thermally stable subsurface microrefuges decoupled from regional climates are the mechanism by which American pikas persist in otherwise inhospitable conditions along the range periphery. Our study advances this line of inquiry beyond previous studies that have shown that subsurface microclimates are decoupled from aboveground climates (Hall et al., ; Henry et al., ; Millar et al., , ; Shi et al., ; Varner & Dearing, ) and dispersal habitats (Millar et al., ) by demonstrating important differences in microclimates among used and unused sites and substrate types.…”
Section: Discussionsupporting
confidence: 76%
“…Contrary to our predictions, pikas exposed to higher daytime temperatures did not increase food-collecting activity at night. At night, interstitial spaces in the talus are warmer than ambient temperatures (Hall et al, 2016;Millar, Westfall, & Delany, 2016). Nocturnally active pikas may also be exposed to increased thermoregulatory costs.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 10 sites from a candidate set of 25 where both pikas were present (determined from occurrence surveys) and we had year-round, in situ thermal profiles -2012Hall, Chalfoun, Beever, & Loosen, 2016). We evaluated temperature data from loggers deployed 50 cm below the surface of the talus at each candidate location and selected sites that encompassed a range of temperatures during the snow-free period (1 June-30 September; range of mean temperatures at selected sites = 8.5-16.…”
Section: Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past work has described migration, tolerance, evolutionary adaptation, and extinction as the range of species responses to climate change [16,26]. We expand on these species responses by considering an increasingly clear and distinct microrefugia response [27][28][29], and by dropping extinction as a response, as it is effectively the consequence of a lack of response. In this ecologicallybased formulation, species vulnerability is the degree to which a species is unable to exhibit any of the four responses necessary for persistence: 1) the migration response, in which a species follows (in a biogeographical sense) its moving climatic limits through dispersal and establishment in new areas where its niche becomes available [30][31][32]; 2) the microrefugia response, when the niche of a species persists in locations that retain suitable climate characteristics [27,[33][34][35] within a greater area that becomes unsuitable at the macro-climatic scale; 3) the toleration response, a situation when climate shifts fit within a species niche breadth [36][37][38][39]; 4) and the evolutionary adaptation response, when a species alters its niche to withstand changes in climate through natural selection [40,41].…”
Section: Main Textmentioning
confidence: 99%